If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying cx + h = 0 Solving cx + h = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1h' to each side of the equation. cx + h + -1h = 0 + -1h Combine like terms: h + -1h = 0 cx + 0 = 0 + -1h cx = 0 + -1h Remove the zero: cx = -1h Divide each side by 'x'. c = -1hx-1 Simplifying c = -1hx-1
| hc+x=0 | | hx+c=0 | | 2+2x=8+4x | | 0.12*8+78.8=x | | -16=d+21 | | 4(n-3)+2n=12 | | X^3+X^2-25X+12= | | g^3+3g^2-g-3=0 | | X-7=(-53) | | 18y^2+9y-5=0 | | 7x^2-42x-7=0 | | 5x+2x-2=12 | | X-27=(-12) | | ax+s=0 | | 2a^2+5a+3=0 | | 3(x+x)+7-5x=8+(-5)(5x-6x)+23 | | 0.5(x+10)+0.1x=14 | | 42+6h=84 | | -0.6x+0.4x-1=-9 | | -19+-12=x | | 6p^2=864 | | -3y+5=-4y+3 | | 9-4(7x-8x)=-3 | | 22+2r=37+6+x | | 15-4k=12-7k | | 18x^2-27x-5=0 | | n+(n+2)+(n+4)=-84 | | -23=3e-(-9) | | 2x+12-10=12+4x-4 | | z+18=y | | 2+5t=-5 | | 10w-18=42 |